Behavior of the B. malayi microfilariae in the peripheral blood of human carrier in the intergradation area of Mahakam Delta East Kalimantan. - FA Sudjadi, FA Sudjadi (Universitas Gadjah Mada, 2002)
Background: Nonperiodic form of B. malayi of human parasite was recently identified in East Kalimantan by Sudjadi as different subspecies in addition to the previously known periodic and subperiodic form of infraspecific variation.Objectives: To detect any changes in microfilarial periodicity in the intergradation area of Mahakam delta with the subperiodic type from South Sulawesi, genealogically related to local population. Methods: Periodicity examinations were carried out on the microfilarial carriers discovered in the B. malayi endemic area of Mahakam delta. Blood examinations (60 mm3 blood) was carried out every 2 hours, in 24 hour cycles. Result analysis was performed using Aikat and Das statistical formula. Results: Six microfilaria carriers of B. malayi were examined for periodicity study. Cases of the nonharmonic or noncircadian form were predominantly (in 5 cases) recorded and only in one case the microfilariae were showed a harmonic or circadian wave pattern,, but with a peak hour at day time, ie 15.5400